Brain based learning with contextual approach to mathematics achievement - V Kartikaningtyas; T A Kusmayadi; Riyadi Riyadi (International Journal of Science and Applied Science: Conference Series, 2017)
The aim of this study was to know the effect of Brain Based Learning (BBL) with a contextual approach to mathematics achievement. BBL-contextual is the learning model that designed to develop and optimize the brain ability for getting a new concept and solving the real life problem. This study method was a quasi-experiment. The population was the junior high school students. The sample chosen by using stratified cluster random sampling. The sample was 109 students. The data collected through a mathematics achievement test that was given after the treatment. The data analyzed by using one way ANOVA. The results of the study showed that BBL-contextual is better than direct learning on mathematics achievement. It means BBL-contextual could be an effective and innovative model.